Strategi Corporate Social Responsibility Starbucks Indonesia dalam Mengedukasi Para Petani Kopi melalui Program Art In A Cup - Mirza Aulia; Davis Roganda Parlindungan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
In a company or organization has a social responsibility to the environment around the company which can be an opportunity to achieve economic, social and environmental balance as well as to meet the expectations of the company's stakeholders. One thing that can be done is to carry out CSR (Corporate Social Responsibility) through programs Art In a Cup, namely empowerment education for coffee farmers in North Sumatra, especially Karo district. The purpose of this study is to determine the planning and implementation of the CSR Art In a Cup program that Starbucks Indonesia is doing. This study used a qualitative approach with descriptive research methods through interviews, observation, documentation, and librarian studies. The results of the research in this study were seen from Starbucks Indonesia's strategy in creating economic, environmental and social sustainability for farmers using the C.A.F.E Practices system which is Starbucks Indonesia's guideline for implementing the CSR Art In a Cup program and with the existence of a team controller, namely Sumatra Specialty Coffee.